EVALUASI KEBIJAKAN PUBLIK TENTANG PROGRAM PENGEMBANGAN PARIWISATA KABUPATEN LAMPUNG TIMUR - Vivi Alvionita; Ari Darmastuti; Robi Cahyadi K; Syarief Makhya (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2021)
East Lampung Regency is one of the areas in Lampung Province which has developed tourism sector by holding 101 tourism events and festivals in 2018. East Lampung Regency tourism calendar in 2018 is the largest tourist calendar in Lampung Province which has an impact of increasing the number of tourist and revolving money. This study is aimed to see how the evaluation of the tourism development program in East Lampung Regency by evaluating the program in term of input, process, benefits and consequences. This study uses a combination method with a descriptive quantitative approach as the primary approach and qualitative as a secondary approach with the interview method. The results showed that, the development of this program was able to increase the number of tourists quite significantly, increase the GRDP, increase the number of tourist objects, open the business fields, slowly change the bad image of East Lampung Regency, educated the community about to use the foreign languages and spur the community to increase the security of the area. Researchers also found several shortcomings of this program, namely, limited budget and not maximized facilities and infrastructure, no direct contribution from tourism to local revenue, the absence cooperation between tourism industries and still lack of quality and innovation in event and festival that were held. Keywords: Evaluation, Public Policy, Tourism Program.